Prevalence of common gastrointestinal nematode parasites in scavenging pigs of different ages and sexes in Eastern Centre province, Burkina Faso - H.H. Tamboura; H. Banga-Mboko; D. Maes; I. Youssao; A. Traore; B. Bayala; M.A. Dembele (Onderstepoort Journal of Veterinary Research, 2006)
The range and infestation intensities of gastrointestinal parasitic nematode species depend on the type of swine production system. The present study focused mainly on nematodes of veterinary importance in scavenging pigs in Burkina Faso, and aimed at determining the prevalence of gastro-intestinal nematode parasites by means of faecal egg per gram (EPG) counts. Between November 2001 and October 2002, faecal samples from 383 pigs of different sexes and ages (< 5 months, 5-12 months and > 12 months) were collected from the rectum and examined for gastrointestinal nematodes parasites using the Mc Master method. Of the 383 pigs examined, 91 % were infected by one or more para sites. Ascaris suum (40 %; 100-1 400 EPG) was the most prevalent parasite followed by Strongyloides ransomi (21 %; 100-4 200 EPG), Oesophagostomum spp. (18 %; 100-1 000 EPG), Hyostrongylus rubidus (11 %; 100-1 800 EPG), Globocephalus spp. 10 %; 100-400 EPG) and Trichuris suis (1 %; 100-200 EPG). The prevalence was significantly higher in female pigs (n = 239) than in males. In addition, females excreted significantly (P < 0.05) more eggs in their faeces than males, except in the case of Globocephalus spp. The age of the animal had no effect on the prevalence of A. suum whereas there were significant differences in age categories concerning S. ransomi, H. rubidus, Oesophagostumum spp. and Globocephalus spp. Unexpectedly, the high prevalence of these common parasites was not accompanied by elevated EPG values, which suggests the existence of moderate infestations. The present work indicates that the common nematode infestations in pigs do not necessarily need a systematic herd anthelmintic treatment, as only a small number of worms is required to induce immunity. A further study is needed to formulate appropriate and cost-effective strategies for the control of gastro-intestinal nematode parasites in pigs in Burkina Faso.